The Naming Book - Flowers, Brad (Ascent Audio, 2020)
NAME YOUR BUSINESS. TELL YOUR STORY. Advertising and marketing masters from Ogilvy to Godin have proven the value of words when it comes to building a brand, attracting an audience, and making a sale. In our increasingly crowded and noisy world, a name is the foundation of every product, brand, or business-and it needs to stand out. In The Naming Book, Bullhorn Creative founder and partner Brad Flowers presents a clear framework for crafting and choosing the name that sticks. With a five-step blueprint that takes you from brainstorming to trademarking, this book is the ultimate guidebook to naming anything. You'll learn how to: set clear goals for your name and brand before you start, craft a brainstorming list based on your business mission, build a brand unique to you by creating your own word, find the balance between "cool" and clear, and narrow down your list of names with five easy tests.
Online resource; Title from title page (viewed October 27, 2020)
Keywords: Business; Affaires; businesses (business enterprises); Audiobooks